HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU DENGAN KEPATUHAN JADWAL PENYUNTIKAN ULANG DEPO PROGESTIN DI PUSKESMAS KASSI¬-KASSI MAKASSAR - Aisyah aisyah (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
Objective: This study aims to determine the relationship of knowledge and attitude of the mother with the compliance of Progestin Depo reinjection schedule at Kassi-Kassi Makassar Public Health Center. Method: This is an analytical descriptive research with Cross Sectional Study approach. The population in this study were all women injecting contraceptive Depo Progestin in the working area of ??Kassi-Kassi Puskesmas Makassar. The number of samples in this study were 61 respondents. Sampling is done by (Accidental Sampling). Data from this research are obtained from primary and secondary data. Furthermore, the data in the analysis using Chi-Square test. Result: The results of this study show that from 61 respondents 49 (80.3%) respondents who have good knowledge and obedient in reinjection, and from 61 respondents as many as 46 (75.4%) respondents who have good attitude and obedient to reinjection. The variables associated with compliance reinjection schedule in this study is knowledge (p = 0.001) attitude (p = 0.00). Discussion: Globally, modern contraceptive users have increased significantly from 54% to 57.4%. Based on the results of Indonesia Demographic and Health Survey (SDKI) showed that the most use of contraception is injectable contraception, that is 49,93%. Injectable contraception is very effective in preventing the occurrence of pregnancy but in its use should be noticed because the problem that often occurs in contraception suntiik is delayed acceptor kb get the injection. Suggestion: The suggestion that can be given from the result of this research is especially for midwives to consider to improve the provision of counseling about counter contraception tool especially KB Injection and for the patient should remain obedient in doing repeated injection and conduct health behavior that can prevent things that are not wanted